Electrophysiological findings in patients envenomed following the bite of a Papuan taipan (Oxyuranus scutellatus canni). - Trevett, A; Lalloo, D; Nwokolo, N; Naraqi, S; Kevau, I; Theakston, R; Warrell, D (1995)
Electrophysiological studies were done on patients with systemic neurotoxicity following the bite of a Papuan taipan (Oxyuranus scutellatus canni). Evoked compound muscle action potentials decreased and increased in tandem with clinical deterioration and recovery. Nerve conduction velocities did not change in envenomed patients and were consistent with control studies. Repetitive nerve stimulation studies showed decremental responses in envenomed patients with post-tetanic potentiation followed by post-tetanic exhaustion. The findings are consistent with studies in vitro which suggested that the major action of neurotoxins in Australian taipan venom is at the synapse. The observation that electrophysiological data correlate closely with the clinical condition of the patient has potential application in the assessment of interventions in the management of snake bite victims.